Ground Movements Associated With Pillar Extraction Coal Mining In Northern West Virginia (38f818ad-9d3b-4ecb-b624-667cef121309) - Robert W. Bruhn (International Conference on Ground Control in Mining, 1984)
An investigation was male of ground response to pillar retreat mining in a 1.7 meter thick seam at 108 meter depth at a site in northern West Virginia. This paper describes mining-related stress changes and movements at nine level, displacements within the overburden, ground surface subsidence and groundwater level variations. Subsidence approached 40 per cent of the nine height ad continued more than a year after mining. Water levels declined la certain deep-lying strata.